Complete mitochondrial genome of an aquatic moth, Elophila interruptalis (Lepidoptera: Crambidae). (August 2014) - Park, Jeong Sun; Kim, Min Jee; Kim, Sung-Soo; Kim, Iksoo
Abstract The aquatic moth, Elophila interruptalis (Lepidoptera: Crambidae) belongs to the subfamily Nymphulinae, nearly all of which are aquatic in their entire larval and pupal stages. The 15, 351-bp long complete mitogenome consisted of a typical set of genes (13 protein-coding genes, two rRNA genes and 22 tRNA genes) and one major non-coding A+T-rich region, with the typical arrangement found in the majority of Lepidoptera. One of the unusual features of the E. interruptalis mitogenome is the presence of a tRNAPhe-like sequence beyond the A+T-rich region. The sequence is encoded in the minor strand of the genome overlapping with the reversely encoded regular tRNAGlu by 65 bp. The sequence divergence of the tRNAPhe-like sequence to that of regular E. interruptalis tRNAPhe and other within-familial species was as low as 59% ∼ 71%, but has a proper folding structure with well-matched stems and identical anticodon sequences to the regular copy.